ANALISIS PENERAPAN GAYA KEPEMIMPINAN KEPALA RUMAH TAHANAN NEGARA KLAS IIB MAGETAN - Faizal Andriawan; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
This study aims to examine the implementation of the leadership style used by the Head of the Class IIB Magetan State Detention Center. In this study, data collection techniques were used by interviewing, documentation and observation. In this study using 5 informants. The informants consisted of the Head of the Class IIB Magetan Rutan and 4 employees of the Magetan Class IIB Rutan. This study used descriptive qualitative method. In this study the concept used is the leadership style according to Lippit & White, namely: 1. Democratic style, in leading, involving all employees in decision making 2. Authoritarian style, in leading, decision making is carried out by the leader himself and for all subordinates operating work on all policies set. 3. Laissez Faire Style, In leading, the leader gives openness & freedom to subordinates both in planning and operationally in carrying out organizational activities. According to the results of the research, the Head of the Class IIB Magetan State Detention Center is greater in applying the Democratic leadership style, for the other two styles, Head of magetan state detention center is applied in certain situations and conditions.